Utilization of Diatom Frustule Waste from Navicula sp. TAD as Photoelectrode Material for Enhancing the Efficiency of Dye-Sensitized Solar Cells (DSSC) - Telussa, Ivonne; Tehubijuluw, Hellna; Lilipaly, Eka Rahmat Mahayani Anthonia Putera; Malle, Dominggus; Amarduan, Riona Magdalena (Science and Technology Indonesia, 2026)
Navicula sp. TAD is a microalga with silica-based cell walls, offering potential to improve photon interaction in dye-sensitized solar cells (DSSCs). This study combined Navicula sp. TAD frustules with TiO2 to fabricate DSSC working electrodes. The objectives were to isolate and characterize the frustules, optimize the TiO2–frustule ratio, and evaluate photoelectric performance. The workflow consisted of cultivating Navicula sp., isolating pigments and frustules, fabricating solar cells with varied electrode compositions, and performing photoelectric testing under a solar simulator. Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), and Scanning Electron Microscope (SEM) analysis confirmed that the frustules possess nanoporous surfaces and exhibit Si–O–Si and Si–OH functional groups. Electrodes incorporating TiO2–frustule blends showed compact pore networks, along with additional functional groups. Performance screening across compositions identified an optimal TiO2–frustule ratio of 40:60, which delivered an efficiency of 10.51%, a short-circuit current density of 0.673 A, an open-circuit voltage of 301.8 mV, and a fill factor of 0.32. These findings indicate that frustule-enabled light management and surface chemistry can jointly enhance dye loading and charge collection in DSSC photoanodes relative to TiO2 alone.